PENGARUH CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PADA SEKTOR FINANCE (Studi pada Perusahaan Sektor Finance yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Illinova, Julian Arsyad; Nuzula, Nila Firdausi (Profit: Jurnal Adminsitrasi Bisnis, 2022)
A study by McKinsey stated that funding sector managers in Asia would finance 26-30% more for firms that have better Corporate Governance. In the Corporate Governance Scores Ranking in Asia Period 2016 and 2018, Indonesia still stands as the last rank, the 12th rank. However, Indonesia could contribute to two firms from the finance sector only at the Top 50 ASEAN CG Conference & Awards 2015. It shows that Indonesia is still lagging compared to other countries in ASEAN and Asia in Corporate Governance, and the finance sector is the leading sector in Indonesia. Data analysis technique using MLR Analysis. The Firm Sample of this research was taken from 27 Finance Firms that are registered within ISE Year 2016-2018. This Research has purposes for establishing the Impact of CG through BOC Independent, BOD, Audit Committee, and Implementation of Public Firm Governance Guidelines against Profitability through ROA and ROE in Finance Firms.